(untitled) (Stato, Chiese e pluralismo confessionale, 2017)
Contributo sottoposto a valutazione SOMMARIO: 1. “Religious lawyering”: la lotta per un movimento accademico – 2. Il possibile ruolo della religione nella deontologia forense – 3. Le critiche della concezione tradizionale e l’idea della morale di ruolo – 4. Problemi teologici di traduzione in forma deontologica – 5. Argomenti religiosi e dibattito pubblico di legal ethics. “Juristen, böse Christen (?)”. Religion and Legal Ethics in the Theory of Law. ABSTRACT: This article focus on the question of whether religious studies contribute to legal ethics and professional lawyer’s life. Notoriously, religion’s role in legal ethics is difficult to define, also because many scholars, belonging to the standard dominant view, disagree about the same nature of legal ethics concepts. Beginning in the late 1970s and especially during the 1990s, the emerging religious lawyering movement started to analyzes whether and how religion values could be integrated into day-to-day law practice. Today, this academic movement challenges the morality-role idea and try to claim a public dimension for the religious commitment.